Flüchtlinge: Opfer – Bedrohung – Helden: Zur politischen Imagination des Fremden - Friese, Heidrun (transcript, 2017)
How the power of linguistic figures shapes sociopolitical debates becomes remarkably clear in contemporary discussions about refugees who are seeking safe harbor in Europe. Heidrun Friese looks into the controversial imaginations of refugees in our society: the figure of the `stranger' as menace articulates the racism of populism and legitimates security policies. Humanitarian, religious and ethical activity on the other hand conceives of refugees as victims in need of help. In a third perspective, the transgression of borders is stylized as a heroic act and ascribed to anti-capitalist struggles. This essay intervenes in this key discourse of the post-migration society and confronts these imagined figures of the `foreign', which in various ways deny the refugees a subjectivity of their own, with another understanding of flight: flight as the mobile site of politics.